Young’s modulus and hardness of multiphase CaZrO3-MgO ceramics by micro and nanoindentation - Silva, Abílio P. (2018)
The aim of this work is to determine the values of the hardness and elastic modulus of the phases present in CaZrO3-MgO-ZrO2 composites and to analyse their contribution to the composite properties. Two materials previously developed with the same major phases (CaZrO3, MgO and c-ZrO2) present in different volume fractions and grain size have been analysed. The hardness and Young’s modulus of each phase determined by nanoindentation are independent from the specific composite and coincident with nanoindentation values for single phase bulk materials. The contribution of the individual phases to Young’s modulus of the multiphase materials is in agreement with calculations using the nanoindentation values and the Voight upper limit of the “rule of mixtures”. Scale effect due to microcracking has been observed for micro-hardness values of the composites and differences between calculations and experimental values are related to this effect.